Peritoneal Dialysis in Extremely Obese Patient From Palestine, A Case Report (Iranian Journal of Kidney Diseases, 2020)
Introduction. The incidence of ESRD is increasing dramatically and the majority of patients are commenced to hemodialysis (HD) or peritoneal dialysis (PD) due to the long waiting time for renal transplantation. PD has comparable outcomes with HD but many barriers limit its utilization. Obesity is considered among the barriers and this was attributed to its related complications. Case Report. A 50-year-old male patient with ESRD presented to our hospital for PD. He was extremely obese (BMI = 44.2 kg/m2). The case was discussed between the nephrology, surgical and nursing team, and the decision was made to proceed towards PD. Conclusion. Obesity should not impede the beneficial effects of PD. The obstacles of obesity, which we faced; could be overcome with the collaboration between a highly qualified multidisciplinary team.